Productive Manipulation of Cyanine Dye π‐Networks. Issue 27 (24th May 2019) - Usama, Syed Muhammad; Thompson, Tye; Burgess, Kevin
Abstract: Polymethine bridges in cyanine dyes may be constrained by setting them into edge‐fused ring systems, or extended by conjugation with carefully chosen heterocycles. Recent studies have shown that modifications like these can give significantly brighter dyes with red‐shifted absorbance and emission maxima. Abstract : Polymethine bridges in cyanine dyes may be constrained by setting them into edge‐fused ring systems, or extended by conjugation with carefully chosen heterocycles. Recent studies have shown that modifications like these can give significantly brighter dyes with red‐shifted absorbance and emission maxima.